“Domestic drama,” “Love killing,” or “Murder”: does the framing of femicides affect readers’ emotional and cognitive responses to the crime? - Schnepf, Julia; Christmann, Ursula (Violence against women, 2023)
We conducted two framing experiments to test how downplaying femicide frames affect readers? reactions. Results of Study 1 (Germany, N?=?158) indicate that emotional reactions were increased when a femicide was labeled as ?murder? compared to ?domestic drama.? This effect was strongest among individuals with high hostile sexism. Study 2 (U.S., N?=?207), revealed that male compared to female readers perceived a male perpetrator more as a loving person when the crime was labeled as ?love killing? compared to ?murder.? This tendency was linked to higher victim blaming. We recommend reporting guidelines to overcome the trivialization of femicides.
Gesehen am 06.03.2023